2018
DOI: 10.1016/j.anaerobe.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Clostridioides (Clostridium) difficile VanZ ortholog, CD1240

Abstract: Clostridioides (Clostridium) difficile causes severe diarrheal disease that is directly associated with antibiotic use and resistance. Although C. difficile demonstrates intrinsic resistance to many antimicrobials, few genetic mechanisms of resistance have been characterized in this pathogen. In this study, we investigated the putative resistance factor, CD1240 (VanZ1), an ortholog of the teicoplanin resistance factor, VanZ, of Enterococcus faecium. In C. difficile, the vanZ1 gene is located within the skin el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Surprisingly, when expressed in S. aureus, enterococcal genomic vanZ g , which is not associated with any glycopeptide resistance gene cluster, was more efficient in conferring resistance to TEI than vanZ Tei ( Table 1). In addition to E. faecium and S. pneumoniae, the involvement of genomic vanZ genes in the resistance to lipoglycopeptide antibiotics was reported for orthologs from Streptococcus suis and Clostridium difficile (Lai et al, 2017;Woods et al, 2018; Supplementary Figure S2). In addition to resistance, VanZ proteins might play a more general role in stress response and virulence, as it was observed that the expression of the streptococcal vanZ gene was induced by the epithelial antimicrobial peptide LL37 (Lai et al, 2017) and ribosome-targeting antibiotics (Ng et al, 2003) or was essential for lung infection (Hava and Camilli, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…Surprisingly, when expressed in S. aureus, enterococcal genomic vanZ g , which is not associated with any glycopeptide resistance gene cluster, was more efficient in conferring resistance to TEI than vanZ Tei ( Table 1). In addition to E. faecium and S. pneumoniae, the involvement of genomic vanZ genes in the resistance to lipoglycopeptide antibiotics was reported for orthologs from Streptococcus suis and Clostridium difficile (Lai et al, 2017;Woods et al, 2018; Supplementary Figure S2). In addition to resistance, VanZ proteins might play a more general role in stress response and virulence, as it was observed that the expression of the streptococcal vanZ gene was induced by the epithelial antimicrobial peptide LL37 (Lai et al, 2017) and ribosome-targeting antibiotics (Ng et al, 2003) or was essential for lung infection (Hava and Camilli, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…The corresponding VanZ F protein shared 21% primary sequence identity with VanZ A but the significance of this protein in the resistance cascade remains unknown. In Clostridiodes difficile a VanZ homologue CD1240 (38% identity to VanZ A ) is encoded on the chromosome outside the van regulon and was shown to be required for resistance to teicoplanin but not to vancomycin . These three VanZ orthologs belong to the “VanZ superfamily” (PF04892 in Pfam), which comprises 7,428 sequences present in Firmucutes (Bacilli, Clostridia, Proteobacteria and Bacteroidetes) and Actinobacteria.…”
Section: Vancomycin Resistance Mechanisms: Two Main Routes For Modifimentioning
confidence: 99%
“…In Clostridiodes difficile a VanZ homologue CD1240 (38% identity to VanZ A ) is encoded on the chromosome outside the van regulon and was shown to be required for resistance to teicoplanin but not to vancomycin. 71 These three VanZ orthologs belong to the "VanZ superfamily" (PF04892 in Pfam), which comprises 7,428 sequences present in Firmucutes (Bacilli, Clostridia, Proteobacteria and Bacteroidetes) and Actinobacteria. While the majority of these proteins are comprised of VanZ sequence exclusively, some representatives combine the VanZ sequence with RDD domain (PF06271), which is a domain also of unknown function.…”
Section: Vanzmentioning
confidence: 99%
“…GI1 possesses several gene attributes that may confer competitive advantage to the RT106 clade. It harbors a vanZ allele, distinct from vanZ1 (49% identity) present elsewhere in RT106 genome and in other C. difficile strains including the well-studied 630 (57). In 630, VanZ1 was previously shown to confer low level resistance to the glycopeptide antibiotic, teicoplanin, but not to vancomycin (57).…”
Section: Discussionmentioning
confidence: 99%
“…It harbors a vanZ allele, distinct from vanZ1 (49% identity) present elsewhere in RT106 genome and in other C. difficile strains including the well-studied 630 (57). In 630, VanZ1 was previously shown to confer low level resistance to the glycopeptide antibiotic, teicoplanin, but not to vancomycin (57). The presence of a second VanZ allele may contribute to the modest increase in teicoplanin resistance of RT106 strains.…”
Section: Discussionmentioning
confidence: 99%